Analysis of Watermelon (Citrullus vulgaris Schard.) Farming Business in Amara Jaya Farmer Group in Binawidya District, Pekanbaru City - Khaswarina, Shorea; Kusumawaty, Yeni; Sihombing, Andre Saputra Hasiholan (Jurnal Natur Indonesia, 2025)
This study analyses watermelon farming in the Amara Jaya Farmer Group in Binawidya District, Pekanbaru City, focusing on farmer characteristics, conformity of cultivation techniques with Good Agricultural Practices (GAP), as well as analysis of costs, revenues, and farming efficiency. Watermelon is a horticultural commodity that has the potential to increase income, but management efficiency is very important. This analytical descriptive research used a case study approach with in-depth interviews with five farmers and secondary data. Results showed an average total production cost of IDR 244,646,434 per hectare per growing season, with an average total revenue of IDR 119,833,333.40 per hectare. The average net income was IDR 125,296,100.00 per growing season. The R/C ratio of 0.184 indicates that the watermelon farm has not broken even and is still losing money, despite the gross profit margin per kilogram